PEMBERDAYAAN PENGRAJIN PRODUK APEM DI DESA KADUBUNGBANG-CIMANUK-PANDEGLANG - Akhmad Nidhomuz Zaman; Santika Sari; Fitri Wahyuni; Noverdo Saputra (Universitas Kadiri, 2020)
ABSTRACTThe development of the industrial center area is one of the efforts to build a local economythat aims to construct commodity-based production of the village that is owned by the localcommunity. Community Service (PKM) is carried out in Kadubungbang-PandeglangVillage. PKM is done to assist in the empowerment of typical Pandeglang culinary businessin the home industry